RAGAM BASA SUNDA DIALÉK SOSIAL KARAWANG DINA BUKU KUMPULAN CARPON KARYA DARPAN: Ulikan Struktur jeung Léksikosemantik - Dessy Nurhabibah, - (2023)
The variety of Karawang social dialect needs to be mastered and analyzed seriously. Efforts to resolve the Karwang social dialect in literary works are very important. The purpose of this study is to describe and compare Karawang social dialects based on language variety, word categories/forms, and lexicosemantic comparisons in a collection of short stories by Darpan. This research includes qualitative research using descriptive methods, data collected using card data. Sales techniques used are equivalent and distributional methods. From the 229 data found, there were six forms of base variety found, namely akrolék, basilék, vulgar, slang, colloquial, and jargon. Judging from the form of the word base, affixes, repeated words, and compound words. Furthermore, the Karawang social dialect is compared to lulugu Sundanese in terms of phonological (37 words), morphological (88 words), and lexical (101 words) aspects. From the results of the comparison, it can be seen that the Karawang social dialect language has a word specificity that is different from lulugu Sundanese. Keywords: dialect, lexicosemantics, variety of languages.